Dampak Deforestasi Terhadap Produksi Listrik PLTA Bakaru Sulawesi Selatan (An Impact of Deforestation on Electricity Production of The Bakaru Hydropower, South Sulawesi) - Rosmaeni; Irlan; Widyanti Utami Adhisti (Jurnal Penelitian Pengelolaan Daerah Aliran Sungai (Journal of Watershed Management Research), 2024)
Deforestation affects the hydrological response of a watershed. Changes in forest land cover to non-forest can degrade watershed functions, especially the condition of water discharge. This research aims to analyze the impact of deforestation in the Mamasa Sub-watershed on the electricity production of the Bakaru Hydroelectric Power Plant. This research method uses the Soil and Water Assessment Tool (SWAT) modeling system. The SWAT model is used to analyze the impact of deforestation on watershed discharge conditions. The deforestation scenario is determined based on the spatial analysis (overlay) results to obtain data on changes in forest land cover to non-forest. Four deforestation scenarios will be generated: no deforestation or zero deforestation (0%), low deforestation (20%), medium deforestation (40%), and high deforestation (60%). The simulation results show that the number of Hydrological Response Units (HRU) will be lower when deforestation increases. This research also succeeded in analyzing the impact of various deforestation scenarios on the electricity production of the Bakaru Hydroelectric Power Plant. The simulation results of the Bakaru hydroelectric power plant's monthly average electricity production tend to be greater when compared to the actual monthly average electricity production. The highest difference in electricity production from the Bakaru hydroelectric power plant for all scenarios occurs in the dry months with an average difference between 802,709.64–2,222,293.19 kWH.